Management of Immune-Mediated Paraneoplastic Neurological Disorders - Ayzenberg, Ilya; Gold, Ralf; Kleiter, Ingo (Neurology International Open, 2017)
Paraneoplastic neurological disorders are rare and clinically heterogeneous diseases. They can affect both the central and peripheral nervous system as well as the neuromuscular junction and muscle. Neurological deficits develop in 2/3 of cases prior to cancer diagnosis. The diagnostic approach includes screening for antineuronal antibodies and a search for the underlying tumor. A prompt tumor therapy in combination with immunotherapy is the cornerstone in the management of these diseases. Due to lack of clinical trials, treatment recommendations are based on case series and expert opinions. High-dose corticosteroids, intravenous immunoglobulins and apheresis therapies are often used in the acute stage of the disease. These therapies should be started as early as possible, e. g., during tumor screening, in order to prevent irreversible damage. Long-term treatment is mostly immunosuppressive and depends on the specific paraneoplastic syndrome. Outcomes vary depending upon the prognosis of the underlying cancer and the nature of the antineuronal antibodies. Disorders with antibodies directed against antigens on the neuronal cell surface are highly sensitive to B cell-directed therapies and mostly associated with a favorable outcome. A thorough review of published data on actual treatment recommendation is provided along with discussion of currently not validated, but potentially effective new therapies.
Keywords: paraneoplastic; autoantibody; encephalitis; polyneuropathy